The advertisement call of Phyllodytes gyrinaethes Peixoto, Caramaschi & Freire, 2003 (Anura, Hylidae) - Roberto, Igor J.; Ávila, Robson W. (Zootaxa, 2013)
Phyllodytes gyrinaethes Peixoto, Caramaschi & Freire, 2003 is an endemic species from the Atlantic Forest of Northeast Brazil, occurring in the states of Alagoas and Pernambuco (Freire & Peixoto 2004). The red color pattern on the inguinal region and concealed surfaces of the hind limbs together with a highly modified tadpole makes P. gyrinaethes the most different species of the genus (Peixoto et al. 2003), being unique and in its own species group according to Caramaschi et al. (2004).